Statistical Entropy of Quantum Black Holes in the Presence of Quantum Gravity Effects - A. D. Kamali; H. Shababi (Advances in High Energy Physics)
We investigate the effects of deformed algebra, admitted from minimal length, on canonical description of quantum black holes. Using the modified partition function in the presence of all orders of the Planck length, we calculate the thermodynamical properties of quantum black holes. Moreover, after obtaining some thermodynamical quantities including internal energy, entropy, and heat capacity, we conclude that, at high temperature limits due to the decreasing of the number of microstates, the entropy tends to upper bounds.